Jangkauan Wilayah Pelayanan Pasar Tradisional Somoroto di Kecamatan Kauman Kabupaten Ponorogo - Abbima Indra Nurcahya (Department of Urban and Regional Planning, Diponegoro University, 2014)
Traditional markets are trading places which still have the original characteristics of traditional trade in accordance with the local culture. Because a number of changes to meet the needs of society, the merchandises that are bought and sold in traditional markets is not only local genuine goods. The merchandises mostly coming from other regions and even comes from large-scale industrial products. This study aims to determine the service coverage of Somoroto traditional market in Kauman Subdistrict, Ponorogo District using mixed methods: quantitative and qualitative descriptive analysis. First, analysis of the mechanism or process of buying and selling goods. Second, analysis of location choosing traders and buyers in the shop at traditional markets Somoroto. Third, the analysis of the origin of traders and buyers. Fourth, the service area network analysis Somoroto traditional markets. The results of this study are as follows: first, as a collection of commodity distribution, Somoroto traditional markets have commodities and scope of different services. Second, most of the merchandises is imported from outside of the Kauman sub-district and Ponorogo district. Third, selling mechanism that characterizes the local culture as “nempur”, “ngutang” and “nempil” are still applied. Fourth, the reason for choosing location in Somoroto traditional markets is not merely a cheap price, but also the ties to social interaction.